Understanding Decision Making about Breast Cancer Prevention in Action: The Intersection of Perceived Risk, Perceived Control, and Social Context: NRG Oncology/NSABP DMP-1. (April 2019) - Gunn, Christine M.; Bokhour, Barbara G.; Parker, Victoria A.; Battaglia, Tracy A.; Parker, Patricia A.; Fagerlin, Angela; McCaskill-Stevens, Worta; Bandos, Hanna; Blakeslee, Sarah B.; Holmberg, Christine
Background. Literature on decision making about breast cancer prevention focuses on individual perceptions and attitudes that predict chemoprevention use, rather than the process by which women decide whether to take risk-reducing medications. This secondary analysis aimed to understand how women's perceptions of breast cancer risk and locus of control influence their decision making.Methods. Women were accrued as part of the NRG Oncology/National Surgical Adjuvant Breast and Bowel Project Decision-Making Project 1, a study aimed at understanding contributors to chemoprevention uptake. Thirty women participated in qualitative in-depth interviews after being counseled about chemoprevention. Deductive codes grouped women based on dimensions of risk perception and locus of control. We used a constant comparative method to make connections among inductive themes focused on decision making, deductive codes for perceived risk and perceived locus of control, and the influence of explanatory models within and across participants.Results. Participants were predominantly non-Hispanic white (63%), with an average age of 50.9 years. Decision making varied across groups: the high-perceived risk/high-perceived control group used "social evidence" to model the behaviors of others. High-perceived risk/low-perceived control women made decisions based on beliefs about treatment, rooted in the experiences of social contacts. The low-perceived risk/low-perceived control group interpreted signs of risk as part of the normal continuum of bodily changes in comparison to others. Low-perceived risk/high-perceived control women focused on maintaining a current healthy trajectory.Conclusion. "Social evidence" plays an important role in the decision-making process that is distinct from emotional aspects. Attending to patients' perceptions of risk and control in conjunction with social context is key to caring for patients at high risk in a way that is evidence based and sensitive to patient preferences.